Safety and performance evaluation of EZVent mechanical ventilator system in hospitalized mechanically ventilated patients: a single-center, open-label, self-controlled clinical trial - Yasser Nassar; Rania A. Galhom; Israa Abdel Raouf; Mohamed Gamal Elansary (The Egyptian Journal of Critical Care Medicine, 2026)
Abstract Background Mechanical ventilation remains a critical intervention for patients with acute respiratory failure, yet selecting optimal ventilation strategies is a challenge. Modern ventilators require rigorous clinical evaluation before widespread adoption. This study evaluated the safety and performance of the novel EZVent ventilator system compared to standard intensive care unit ventilators. Methods This single-center, open-label, non-randomized, self-controlled study was conducted at Al Kasr Al Ainy Hospital, Cairo University (2023–2025). Twenty-two mechanically ventilated adult clinically stable patients with FiO₂ ≤60% and PEEP ≤ 10 cmH₂O were enrolled. Each patient acted as their own control with readings at baseline (T0), after 120 min on EZVent (T2), and 30 min after returning to the standard ventilator (T3). Primary endpoints included arterial blood gas parameters, lung mechanics, and vital signs. Results The underlying conditions of the participants included COPD/bronchial airway disease, pulmonary parenchymal disease, and postoperative causes. Mean duration of ventilation on both ventilators was 3.33 ± 0.36 h. Slight improvements in PaO₂ and mild PaCO₂ rise occurred but were clinically insignificant. SaO₂ remained stable. pH showed a small yet statistically significant reduction but stayed within the normal physiological range. lung mechanics and vital signs showed no statistically significant differences. All variables reverted to baseline at T3, and no serious adverse events were observed. Conclusions EZVent demonstrated safe and effective ventilatory performance comparable to standard ICU ventilators, maintaining stable gas exchange, lung mechanics, and vital signs throughout the study period. These findings support the safety and efficacy of EZVent in mechanically ventilated patients. Clinical trial registration The clinical trial described in this paper was registered at Egyptian Drug Authority, Central Administration of Biological and Innovative products and clinical studies under the registration number MD-004, 28-8-2022, https://www.edaegypt.gov.eg/media/pompzf1h/ct-protocols-registry_4-2026.pdf .